PEMBANGKIT TEGANGAN TINGGI MEMAKAI BEBERAPA TRANSFORMATOR YANG DISUSUN SECARA CASCADE - , HARRY DAMANI, Ir. T. Haryono, M.Sc., C.Eng., MIET. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High voltage test aims to investigate the quality of electrical properties of dielectric insulation system of power equipment, which check the quality of equipment installed before or after operation, to avoid any harm to equipment user and reduce losses during maintenance. High voltage test required high nominal supply voltage. By using multiple transformers which can be found in the market and then arranged as cascade can be produced a high nominal supply voltage. The result, the voltage generated by the system with each unit were not given any compensating winding has fairly good results and ideally close to the value of 880 volts ideally which is 800 volt for the arrangement of four transformers.